Pengaruh Beda Suhu Peletakan Bangkai terhadap Pertumbuhan Larva Lalat Chrysomya Megacephala Pada Tikus Wistar (Rattus norvegicus) - Andi Ipaljri Saputra; Isramilda Isramilda; Sufyan Ats Tsaury (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2022)
Background: Not a few phenomena of abandoned corpses without knowing the length of time of death, to reveal the mystery of abandoned corpses, identification is needed in order to find out post-mortem interval (PMI). With the help of forensic entomologists as investigators and Chrysomya Megacephala flies as the type of animal that first landed on the corpse. The fast or slow growth of flies is also influenced by temperature as the main factor, so by examining the growth of flies with different temperatures, it is possible to calculate the length of time the corpse will die. Methods:This research method is an analytical research true experimental design in the laboratory using the "Posttest Only Control Group Design",The test animals in this study were 18 rats (Rattus norvegicus) which were dislocated in the neck and given an 1cm incision in the abdomen. The treatment was divided into 3 temperature groups, namely 160C, 270C and 390C using an incubator, each of which was placed 10 Chrysomya Megacephala flies. And seen for 5 days in a row in the morning and evening. The analytical test used is the Mann Whitney test. Results:The results obtained when tested using the Mann Whitney test were obtained (p value = 0.010) which means that there is a significant difference between temperatures of 160C and 390C. Meanwhile, at a temperature of 270C with a temperature of 160C and 390C (p value = 0.000), which means that there is a non-significant difference between the treatment at 270C with a temperature of 160C and 390C. Conclusion: Based on the results of this study, it can be concludedthe differences in the growth of Chrysomya Megacephala fly larvae at different temperatures.